APLICAÇÃO DOS CRITÉRIOS DE SUSTENTABILIDADE NAS LICITAÇÕES PÚBLICAS NA UFES: Análise e Propostas - Aguiar, Denner Alves de (2019)
Considering the accelerated growth of environmental degradation, society cries for mechanisms able to ensure the renewal of natural resources and raw materials that are environmentally correct, and to do so it is necessary to promote a change in the patte